Secondary structure of splice sites in adenovirus mRNA precursors. - Munroe, S H (1984)
In order to investigate the possible role of RNA secondary structure in determining the efficiency and specificity of mRNA splicing, the structures of sequences at three acceptor splice sites in adenovirus were studied. Transcripts spanning intron-exon junctions were synthesized using SP6 RNA polymerase and analyzed using single and double-strand specific nucleases. Distinctive patterns of nuclease cleavage were observed for each of the 3 sites examined. At both sites in the E2a region sequences adjacent to the splice sites were particularly susceptible to digestion with T1 and S1 nucleases. In contrast, a splice site for hexon mRNA was largely resistant to these nucleases. The results obtained suggest that the conformation of the RNA at some, but not all, acceptor sites may enhance the accessibility of these sites to factors involved in splicing nuclear RNA and confirm the presence of a large, previously predicted hairpin structure centered on the acceptor site at 67 map units.